Prediksi Jumlah Produksi Kakao Provinsi Aceh dengan Metode Adam Bashforth-Moulton (ABM) - Riezky Purnama Sari; Riska Novita sari (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2023)
Aceh province's cocoa production experiences increases and decreases every year and has not shown significant development even though cocoa has a very important role in supporting the agricultural sector and the economy of Aceh province. The aim of this research is to provide information about estimating the production and supply of cocoa for Aceh province in 2023-2026 with the hope that the government can make more precise plans regarding cocoa and can make Aceh province the largest cocoa producer in Sumatra. This research uses the Adams Bashforth Moulton method which can provide a fairly accurate solution in completing the approximation of cocoa production quantities. Data analysis began by using the fourth order Runge Kutta method to obtain four initial solutions which were then substituted into the fourth order Adams Bashforth predictor equation. The estimation results using the Adams Bashforth Moulton method show that every year the amount of cocoa production increases by an average of 3.67% per year. The predicted cocoa production for Aceh Province in 2023 will be 38451.2 tons, in 2024 it will be 39880.6 tons, in 2025 it will be 41327.5 tons, and in 2026 it will be 42789.6 tons.